Sentinel Lymph Node Imaging, Biopsy in Head/Neck and Breast Cancers: A Comprehensive Review - Palaniswamy Shanmuga Sundaram; Padma Subramanyam (Indian Journal of Nuclear Medicine, 2026)
Sentinel lymph node imaging and biopsy (SLNI and SLNB) have become key components in the management of many solid tumours, especially Head / Neck cancer (HNCa) and breast cancer (BC), offering an accurate and minimally invasive lymph nodal staging. The rationale being that the sentinel lymph node (SLN) is the first draining node from the primary tumour site and, therefore, is the most likely site for early lymphatic dissemination of metastatic tumour cells. SLN identification is conventionally performed using minute amounts of radio colloids either alone or in combination with a vital blue dye, such as - methylene blue dye. Absence of metastatic disease on intraoperative frozen section analysis of the excised SLN obviates the need for complete lymph nodal dissection and its associated postoperative morbidity. Studies have established that SLNI and SLNB reliably detect occult nodal metastases with high sensitivity and have largely replaced routine axillary or cervical lymph nodal dissections. This shift significantly reduces complications such as arm lymphedema, shoulder dysfunction and neuropathic pain in BC cases and postsurgical neck complications in HNCa without compromising the oncologic outcomes. In this review, we shall discuss the procedure, injection techniques and current literature evidence for performing SLN procedures for early HNCa and BC patients.